Design of dictionary based on Discrete Tchebichef Transform - Qayyum A.; Malik A.S.; Nuafal M.; Iqbal M.; Abdullah T.A.R.B.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Signal processing; Basis Pursuits; Discrete Cosine Transform(DCT); Discrete tchebichef transforms; KSVD; Optimization techniques; Orthogonal matching pursuit; Over-complete dictionaries; Root mean square values; Discrete cosine transforms